Menelusuri Manusia Super dari Kesusastraan Tradisional - Eka Meigalia (Jurnal Elektronik WACANA ETNIK, 2012)
This research describe about the superhero people there are in the traditional literature. In Minangkabau traditional literature such as kaba, there are Cindua Mato, Anggun Nan Tongga, and Rambun Pamenan. But they are not familiar, especially for the young generation. This is happen because there no other type from kaba which is easy to understand by the young generation.